1995
DOI: 10.1177/003693309504000505
|View full text |Cite
|
Sign up to set email alerts
|

Home Nebuliser Use in Children with Asthma in Two Scottish Health Board Areas

Abstract: Re-organisation of resources and arrangements could improve the service and bring it in line with recognised standards of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Further, messages from this early look at the literature about some clinical interventions delivered at home were mixed: increased infections in children with cancer cared for at home, 8 but cheaper and equally effective chemotherapy at home; 9 infected nebulisers used for treatment of cystic fibrosis at home, [10][11][12] poorly controlled asthma with home nebulisers, 13 sometimes associated with incorrect use, 14 yet lowered emergency hospital visits and admissions when using home nebulisers for asthma; 15 higher rates of catheter infection in total parenteral nutrition (TPN) at home for children compared with adults, 16 yet less infection in central venous catheters at home than in hospital, 17 and longlasting and safe lines; 18 deep vein thrombosis, 19 embolism and septicaemia 20 in parenteral nutrition; higher rates of contamination in enteral feeds at home than in hospital 21 and poor standards of care for enteral nutrition. 22 By contrast, home ventilation therapy seemed to have a somewhat better 'press' 23,24 with suggestions that, compared with prolonged hospital care, it was both safer and cheaper.…”
Section: The Need For Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, messages from this early look at the literature about some clinical interventions delivered at home were mixed: increased infections in children with cancer cared for at home, 8 but cheaper and equally effective chemotherapy at home; 9 infected nebulisers used for treatment of cystic fibrosis at home, [10][11][12] poorly controlled asthma with home nebulisers, 13 sometimes associated with incorrect use, 14 yet lowered emergency hospital visits and admissions when using home nebulisers for asthma; 15 higher rates of catheter infection in total parenteral nutrition (TPN) at home for children compared with adults, 16 yet less infection in central venous catheters at home than in hospital, 17 and longlasting and safe lines; 18 deep vein thrombosis, 19 embolism and septicaemia 20 in parenteral nutrition; higher rates of contamination in enteral feeds at home than in hospital 21 and poor standards of care for enteral nutrition. 22 By contrast, home ventilation therapy seemed to have a somewhat better 'press' 23,24 with suggestions that, compared with prolonged hospital care, it was both safer and cheaper.…”
Section: The Need For Evaluationmentioning
confidence: 99%
“…Nebulisers can be useful for those having frequent acute attacks or for children who are too young to use simpler devices. 13 However, a survey in the mid-1990s suggested that the provision and management of paediatric nebuliser services are poor and that "with the development of simpler, and less expensive, inhalational devices, nebulisers may even be inappropriate for many…children" 13 (p.143).…”
Section: Nebuliser Therapymentioning
confidence: 99%
“…1, 10-12 Among children with asthma, the prevalence of sleep problems is higher, with 40-60% having some difficulty. 13, 14 Children with asthma are nearly four times more likely to experience sleep disordered breathing (SDB), 15 resulting in sleep disruption and decreased sleep efficiency, 16 reduced sleep quality, increased nighttime activity levels, 17 and more difficulties with daytime sleepiness. 16, 18 Sleep efficiency has been shown to improve with effective treatment of asthma symptoms, 16 but even children with clinically stable asthma have worse sleep quality and more daytime sleepiness than children without asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in asthma care encourage early initiation of home nebulizer use for relief of acute, severe symptoms, especially in young children, 15,18 to decrease ED visits and hospitalization. 19,20 See also pages 977 and 979…”
mentioning
confidence: 99%